Study of SAW Based on a Micro Force Sensor in Wireless Sensor Network. (19th April 2017) - Wang, Jun; Li, Yuanyuan; Chen, Ke; Lu, Wenke; Liu, Qinghong; Zhang, Haoxin; Yan, Huashan
Abstract : Wireless sensor network (WSN) technology has increasingly assumed an active role in detection, identification, location, and tracking applications after more than ten years of development. However, its application still suffers from technology bottlenecks, which must be solved and perfected to eliminate the key problems of the technology. This article investigates WSN acquisition nodes and analyzes the relationship between the frequency and actual pressure values of sensor nodes. The sensitive mechanism of the surface acoustic wave (SAW) based on a micro force sensor is researched, and the principle of least squares method is used to establish a transformation model of frequency and pressure for the SAW sensor. According to the model, polyfit function and matrix calculation are selected to solve and calculate the estimate of the polynomial coefficients, which simulate the data acquisition of WSN nodes and draw a polynomial curve fitting. The actual SAW sensor is tested to demonstrate the reasonableness of the device stability in WSNs.